STUDI DAK KEPARIWISATAAN SEBAGAI POTENSI PENDANAAN SUSTAINABLE TOURISM (Jurnal Ilmiah Pariwisata; Vol 19 No 3 (2014), 2014)
Tourism sector is considered to have a very important role in order to increasing the national income, as well as to leveraging people welfare on the local area. Unfortunately, tourism is also considered as one sector that have a very large environmental damage, associated with the development of a variety of basic infrastructure such as resorts, hotels and roads. Therefore, the trend of future tourism development is sustainable tourism. The problem is, sustainable tourism in various regions always bumping to the funding issue. Therefore, by using descriptive analysis of regulation, the potential of the Special Allocation Fund (DAK) more in-depth analysis as well drafted policy recommendations related to the preparation of DAK of Tourism as one of the sources of funding sustainable tourism in the region in the future. Sektor pariwisata selama ini dianggap memiliki peran yang sangat penting dalam meningkatkan devisa nasional, sekaligus menyejahterakan masyarakat di daerah. Sayangnya, pariwisata juga dianggap sebagai salah satu sektor yang menyumbang kerusakan lingkungan yang sangat besar terkait dengan upaya pembangunan berbagai infrastruktur dasar seperti resort, hotel dan jalan. Karenanya, tren pengembangan pariwisata ke depan adalah pariwisata yang sadar lingkungan ( sustainable tourism ). Permasalahannya, sustainable tourism di berbagai daerah selelu terbentur kepada persoalan pendanaan. Karenanya, dengan menggunakan metode analisis deskriptif regulasi, potensi Dana Alokasi Khusus (DAK) dianalisis lebih mendalam sekaligus disusun rekomendasi kebijakan terkait penyusuna DAK Kepariwisataan sebagai salah satu sumber pendanaan sustainable tourism di daerah ke depannya.
Keywords: Sustainable Tourism, Speciffic Allocation Fund (DAK) , Speciffic allocation Fund for Tourism